Initial testing of the use of the Safer Nursing Care Tool in a Canadian acute care context. (28th March 2021) - Caron, Isabelle; Gélinas, Céline; Boileau, Johanne; Frunchak, Valerie; Casey, Ann; Hurst, Keith
Abstract: Aim: Initial testing of England's Safer Nursing Care Tool for adult in‐patient acute care wards in a university‐affiliated Canadian hospital. Background: Safe‐nursing staffing decisions have significant impacts on patients' safety and quality of care. The Safer Nursing Care Tool was developed in England to provide managers with a validated formula for making appropriate nursing staffing decisions. The tool has been widely used and studied in the UK but has yet to be tested in a Canadian context. Method: Ten high service quality acute care wards from a university‐affiliated Canadian hospital tested the use of the Safer Nursing Care Tool. Service quality, patients' dependency/acuity and staff activity data were benchmarked against information collected in 726 comparable UK wards. Results: Higher bed occupancy and patient dependency/acuity mix were found in the 10 Canadian wards compared to their UK counterparts. Overall staff activity was comparable between UK and Canadian wards. Conclusion: The Safer Nursing Care Tool can be applied in this Canadian hospital, and further testing in other hospitals and specialties is required. Implication for Nursing Management: The Safer Nursing Care Tool is a valid staffing tool to use that, when combined with professional judgement, can help managers to properly establish nursing staff in acute care wards.